Identification of Demographic Variables Influencing Dementia Literacy and Risk Perception Through a Global Survey - Horst, Becky R.; Furlano, Joyla A.; Wong, Michelle Y. S.; Ford, Sabrina D.; Han, Brenna B.; Nagamatsu, Lindsay S. (Frontiers in Public Health, 2021)
Dementia literacy is important for risk mitigation and preventative strategies before disease onset. The aim of our study was to investigate dementia literacy and how demographic characteristics influence these perceptions in order to provide evidence for how dementia-centered public health initiatives should structure their focus. We conducted a globally administered online survey, through Amazon Mechanical Turk (mTurk). Survey items evaluated: (1) personal perception on the preventability of dementia, and (2) risk awareness of lifestyle factors. Differences in risk scoring between the 598 respondents were compared using Kruskal-Wallis testing factored by demographic categorizations. Most of the sample demonstrated understanding that lifestyle factors contribute some risk toward dementia, though these risk scores were generally low. Differences in risk scoring varied by demographic characteristics. Women, older adults, those with non-post-secondary attainment, below average income, and White background tended to report lower risk scores. Public health education and initiatives for dementia prevention should focus on lifestyle risk factors, in addition to considering the barriers related to the demographic factors identified that may prevent populations from accessing programs and information.